Optymalizacja Osiowo-Symetrycznego Ustroju Wiszącego, Zawieszonego na Górnym Pierścieniu - Kempny, S. (Engineering Transactions, 1971)
Here, an optimum shape is sought for an axially symmetrical grid suspended cover, where the volume of the carrier elements possesses a minimum. The system is supported on the upper ring and subjected to the action of a load distributed uniformly over the surface. In the calculations the changes in specific gravity occurring along the longitudinal curves are not taken into account. It is proved that the functional of the volume of carrier ropes has a minimum for such a shape of the longitude at which the forces in the latitudinal lines are equal to zero.